Diagnostics of Piezoelectric Bending Actuators Subjected to Varying Operating Conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Hemsel, Tobias; Sextro, Walter (Electronics)
In applications of piezoelectric actuators and sensors, the dependability and particularly the reliability throughout their lifetime are vital to manufacturers and end-users and are enabled through condition-monitoring approaches. Existing approaches often utilize impedance measurements over a range of frequencies or velocity measurements and require additional equipment or sensors, such as a laser Doppler vibrometer. Furthermore, the non-negligible effects of varying operating conditions are often unconsidered. To minimize the need for additional sensors while maintaining the dependability of piezoelectric bending actuators irrespective of varying operating conditions, an online diagnostics approach is proposed. To this end, time- and frequency-domain features are extracted from monitored current signals to reflect hairline crack development in bending actuators. For validation of applicability, the presented analysis method was evaluated on piezoelectric bending actuators subjected to accelerated lifetime tests at varying voltage amplitudes and under external damping conditions. In the presence of a crack and due to a diminished stiffness, the resonance frequency decreases and the root-mean-square amplitude of the current signal simultaneously abruptly drops during the lifetime tests. Furthermore, the piezoelectric crack surfaces clapping is reflected in higher harmonics of the current signal. Thus, time-domain features and harmonics of the current signals are sufficient to diagnose hairline cracks in the actuators.
Keywords: piezoelectric transducer; self-sensing; fault detection; diagnostics; hairline crack; condition monitoring

Burst Mode of Ultrasonic Resonant Oscillations for Stimulation and Destruction of Tumor Cells - Sehlmeyer, Birte; Kampmann, Rebecca; Scheidemann, Claus; Hemsel, Tobias; Getzlaff, Mathias (Frühjahrstagung 2023, Sektion Kondensierte Materie (SKM))

Burst Mode Characteristics of an Ultrasonic Transducer for Treatment of Cancer Cells - Kampmann, Rebecca; Sehlmeyer, Birte; Scheidemann, Claus; Hemsel, Tobias; Getzlaff, Mathias (Frühjahrstagung 2023, Sektion Kondensierte Marterie (SKM))

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Experimental Investigation of Bond Formation and Wire Deformation in the Ultrasonic Wire Bonding Process - Scheidemann, Claus; Hagedorn, Oliver Ernst Caspar; Hemsel, Tobias; Sextro, Walter

Piezoelectric Ultrasonic Power Transducers - Hemsel, Tobias; Twiefel, Jens (Reference Module in Materials Science and Materials Engineering)
This article is dedicated to piezoelectric ultrasonic power transducers that differ to well known medical ultrasonic diagnostic apparatus or non destructive testing devices by the level of power in use; typically several tens of up to more than thousand watts are used in a multitude of different applications. After a short introduction including historical development, the first focus is on theoretical background of the operating principle, design and mechanical modeling. As piezoelectric elements transform electrical to mechanical energy and vice versa, equivalent circuit modeling is also described. After that, sample applications are delineated by the matter wherein ultrasound generates unique effects: incredible high pressure level as well in air as in water, micro-bubbles generating temperature peaks for very short time instances in fluids, acoustoplastic effect, enhancement of diffusion and recrystallization in solids, friction manipulation, incremental deformation and micro-cracking of surfaces, or even generation of macroscopic movements in motors. At the end, some future directions ranging from novel modeling approaches to advanced control and new materials are addressed.
Keywords: Equivalent circuit model; Langevin transducer; Lumped parameter model; Piezoelectric transducer; Ultrasonic processes; Ultrasound

Experimental Investigation of the Influence of different Bond Tool Grooves on the Bond Quality for Ultrasonic Thick Wire Bonding - Hagedorn, Oliver Ernst Caspar; Broll, Marian; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (CIPS 2022 - 12th International Conference on Integrated Power Electronics Systems)
To achieve optimum bond results at ultrasonic bonding thick copper wire on sensitive components is quite challenging. Bearing in mind that high normal force and ultrasonic power are needed for bond quality but as well increase stress and finally failure risk of the substrate, methods should be found to achieve high bond quality even at lower bond parameters. Therefore, bond experiments with different bond tool grove geometries have been conducted for copper and aluminum wire on direct copper bonded (DCB) substrates to investigate the impact of geometric parameters on bond formation and bond quality. The wire material depending impact of geometry changes on the bond formation and deformation was quantified. Additionally, a bonding parameter design of experiments (DOE) has been conducted for the reference and the most promising groove geometry. Higher shear values were achieved at reduced vertical tool displacement for most bonding parameter combinations, compared to the reference tool. This behavior allows for reducing ultrasonic power to obtain equal shear values; consequently, mechanical stresses in the interface decrease. This could potentially reduce the risk of chip damage and thus yield loss.

Experimental Investigation of Multidimensional Ultrasonic Heavy Wire Bonding - Scheidemann, Claus; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC))
ue to the constantly growing energy demand of power electronics and the need to reduce the size of electronic components like power modules for e-mobility, new challenges arise for ultrasonic wire bonding: the electrical connection must endure higher thermal and mechanical stress while the connecting partners become more sensitive or require more energy to get bonded. Past investigations have shown already that multi-dimensional ultrasonic bonding and welding yield the same or even better bond quality while reducing the load on the components. This contribution is intended to show whether multidi-mensional thick wire bonding is a promising concept to over-come the new challenges. The focus is on experimental investi-gations of different bond tool trajectories in ultrasonic wire bonding of aluminum and copper wire on DCB's and chips. The bond quality is analyzed by shear tests, microsections and, in the case of aluminum bonding, by a new machine learning method for an objective automated evaluation of the sheared area.

Modellbasierte Ermittlung optimaler Prozessparameter für neuartige Ultraschallbondverbindungen - Scheidemann, Claus; Hemsel, Tobias; Sextro, Walter

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Experimental analysis and modelling of bond formation in ultrasonic heavy wire bonding - Schemmel, Reinhard; Scheidemann, Claus; Hemsel, Tobias; Kirsch, Olaf; Sextro, Walter (CIPS 2020; 11th International Conference on Integrated Power Electronics Systems)
Ultrasonic wire bonding is a process to form electrical connections in electronics well established industry. Typically, a clamping tool is pressed on the wire and forced to vibrate at relative high frequency 40 to 100 kHz. The ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes, contamination like oxide layers are removed from the contact zone, the surface roughness is reduced, and with increasing bond duration an metallic connection of wire and substrate is established. It is known that the amount of ultrasonic energy over time directly influences the strength and reliability of the bond connection, but the determination of optimum bond parameters is still a challenging experimental task. For this, in the past different model approaches have been presented, to calculate the bond quality by simulation. Measuring the friction between wire and substrate to validate these models is a challenging task at ultrasonic bonding frequency. Therefore a versatile test rig for bonding experiments at frequencies lower than 1 kHz is setup to get detailed insight into the different phases of the connection process. It includes a piezoelectric force sensor for the measurement of the three-dimensional process forces, an electrodynamic shaker for the vibration excitation and a conventional tension-compression testing machine to apply the bond normal force. Using this test rig, it is possible to observe the different phases of bond formation in detail, validate and enhance existing models and finally optimize bond parameters for different processes.

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (2020 21st International Conference on Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE))

Atomization of Fluids with Ultrasound - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter; Sextro, Walter (Conference Proceedings - The 4th Conference on MicroFluidic Handling Systems (MFHS2019))
In a variety of industrial applications, liquids are atomized to produce aerosols for further processing. Example applications are the coating of surfaces with paints, the application of ultra-thin adhesive layers and the atomization of fuels for the production of combustible dispersions. In this publication different atomizing principles (standing-wave, capillary-wave, vibrating-mesh) are examined and discussed. Using an optimized standing-wave system, tough liquids with viscosities of up to about 100 Pas could be successfully atomized.
Keywords: atomization; ultrasound; standing-wave; capillarywave; vibrating-mesh

Messung hochfrequenter In-Plane-Schwingungen mittels Laservibrometrie in räumlich eingeschränkten Umgebungen - Hagedorn, Oliver Ernst Caspar; Pielsticker, Daniel; Hemsel, Tobias; Sextro, Walter (2. VDI-Fachtagung Schwingungen 2019)

Modellbasierte und experimentelle Charakterisierung von intensiven Ultraschall-Stehwellenfeldern für die Zerstäubung hochviskoser Flüssigkeiten - Dunst, Paul; Hemsel, Tobias; Bornmann, Peter; Littmann, Walter; Sextro, Walter (DAGA 2019)
Für die Zerstäubung hochviskoser Flüssigkeiten werden neben Düsenzerstäubern vor allem UltraschallStehwellenzerstäuber angewendet [1]. Diese ermöglichen ohne weitere Maßnahmen zwar keine gerichtete Zerstäubung, benötigen jedoch im Gegensatz zu Düsenzerstäubern keine hohen Drücke und haben keine hohen Austrittsgeschwindigkeiten. Zur Erzeugung der Ultraschallwellen werden typischerweise piezoelektrische, mit Bolzen verschraubte LangevinWandler verwendet [1-4], die eine starke Schallabstrahlung bei einer elektrischen Eingangsleistung von bis zu einigen Kilowatt erzeugen können. Wie bei jedem anderen schwingenden System emittiert der Ultraschallwandler zunächst eine Wanderwelle. Mit einem Reflektor, der gegenüber der Sonotrode angeordnet ist, wird eine stehende Welle erzeugt. Im Resonanzabstand zwischen Reflektor und Wandler werden abgestrahlte und reflektierte Wellen so überlagert, dass höhere Schalldruckamplituden erzielt werden. Ein einfacher Ansatz zur Maximierung des Schallpegels im Stehwellenfeld ist die Erhöhung der Schwingungsamplituden des Wandlers, die jedoch zu Schäden oder zumindest zu einer Verringerung der Lebensdauer führen kann. Hohe Schalldrücke werden auch bei geringen Abständen zwischen Wandler und Reflektor erreicht. Das Volumen des Schallfeldes ist in diesem Fall jedoch für die meisten Prozesse zu klein. Ein weiterer Ansatz ist die Verwendung zweier entgegengesetzt angeordneter Wandler [5]. In diesem Fall erfordert jedoch die Erzeugung einer stehenden Welle eine genaue Abstimmung von Frequenz und Phase beider Wandler, was eine komplexe Steuerung erfordert. Ebenso ist es möglich, geometrische Randbedingungen des Stehwellensystems zu optimieren, sodass es zu optimaler Interferenz der Wellen kommt. Im Folgenden wird der Anschaulichkeit halber vereinfachend angenommen, dass der Wandler an seiner Sonotrodenoberfläche einzelne Schallstrahlen aussendet, die in Nähe des Wandlers nahezu parallel verlaufen und sich mit zunehmender Entfernung vom Wandler auffächern. Ein einfaches Stehwellensystem, bestehend aus ebener Sonotrode und ebenem Reflektor, erzeugt bei kleinem Abstand zwischen Sonotrode und Reflektor sehr hohe Schallpegel, da nahezu sämtliche ausgesandten Schallstrahlen in Richtung der Sonotrode reflektiert werden positive Interferenz entsteht. Erhöht man jedoch den Abstand zwischen Sonotrode und Reflektor, so nehmen die Verluste durch Schallstrahlen, die den Prozessraum verlassen, zu. Wie Abbildung 1 gezeigt, werden nur Schallstrahlen, die in etwa parallel zur Rotationsachse verlaufen, zum Wandler zurück reflektiert und tragen zum Stehwellenfeld bei. Die Strahlen haben zudem abhängig vom Abstrahlwinkel unterschiedliche Weglängen. Die Stehwellenbedingung ist demnach nur für Strahlen in der Nähe der Rotationsachse exakt erfüllt. Um dies zu vermeiden, müssen die Geometrien von Wandler und Reflektor optimiert werden. In den folgenden Abschnitten wird zunächst ein Optimierungsansatz vorgestellt. Mithilfe eines FiniteElemente-Modells werden die Auswirkungen einer optimierten Geometrie auf den maximalen Schalldruckpegel untersucht. Ergebnisse werden durch Messungen an einem experimentellen Aufbau eines Stehwellensystems validiert. Es wird gezeigt, wie sich die Optimierung der geometrischen Randbedingungen auf die Zerstäubung hochviskoser Flüssigkeiten auswirkt.

Impact of multi-dimensional vibration trajectories on quality and failure modes in ultrasonic bonding - Schemmel, Reinhard; Eacock, Florian; Dymel, Collin; Hemsel, Tobias; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (International Symposium on Microelectronics)
Ultrasonic joining is a common industrial process. To build electrical connections in the electronics industry, uni-axial and torsional ultrasonic vibration have been used to join different types of workpieces for decades. Many influencing factors like ultrasonic power, bond normal force, bond duration and frequency are known to have a high impact on bond quality and reliability. Multi-dimensional bonding has been investigated in the past to increase ultrasonic power and consequently bond strength. This contribution is focused on the comparison of circular, multi-frequency planar and uniaxial vibration trajectories used for ultrasonic bonding of copper pins on copper substrate. Bond quality was analyzed by shear tests, scanning acoustic microscopy and interface cross-sections.

Using complex multi-dimensional vibration trajectories in ultrasonic bonding and welding - Schemmel, Reinhard; Hemsel, Tobias; Dymel, Collin; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (Sensors and Actuators A: Physical)
Ultrasonic joining is a common industrial process. In the electronics industry it is used to form electrical connections, including those of dissimilar materials. Multiple influencing factors in ultrasonic joining are known and extensively investigated; process parameters like ultrasonic power, bond force, and bonding frequency of the ultrasonic vibration are known to have a high impact on a reliable joining process and need to be adapted for each new application with different geometry or materials. This contribution is focused on increasing ultrasonic power transmitted to the interface and keeping mechanical stresses during ultrasonic bonding low by using a multi-dimensional ultrasonic transducer concept. Bonding results for a new designed connector pin in IGBT-modules achieved by multi- and one-dimensional bonding are discussed.
Keywords: Ultrasonic bonding; Ultrasonic welding; Multi-dimensional bonding; Complex vibration; Multi-frequent; Two-dimensional friction model

Vibration Assisted Dosing, Mixing and Transport of Dry Fine Powders - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter.; Sextro, Walter (ACTUATOR 2018; 16th International Conference on New Actuators)
The handling of fine powders is an important task in modern production processes. However, as fine powders strongly tend to adhesion and agglomeration, their processing with conventional methods is difficult or impossible. Especially when processing small amounts of highly sensitive fine powders, conventional methods reach their technical limits. In process steps such as dosing, transport, and especially mixing of fine powders new methods are required. Apart from the well-known method of manipulating powder properties by adding chemical additives, this contribution aims at improving the handling of dry fine powders by using vibrations at different frequencies. Modules are presented, which enable the continuous dosing, the homogeneous mixing and the transport of dry fine powders. Finally, these modules are combined for the production of a homogeneous mixture of two dry fine powders.

Vibration-Assisted Handling of Dry Fine Powders - Dunst, Paul; Bornmann, Peter; Hemsel, Tobias; Sextro, Walter (Actuators 2018, 7(2).)
Abstract:Since ﬁne powders tend strongly to adhesion and agglomeration, their processing withconventional methods is difﬁcult or impossible. Typically, in order to enable the handling of ﬁnepowders, chemicals are added to increase the ﬂowability and reduce adhesion. This contributionshows that instead of additives also vibrations can be used to increase the ﬂowability, to reduceadhesion and cohesion, and thus to enable or improve processes such as precision dosing, mixing,and transport of very ﬁne powders. The methods for manipulating powder properties are describedin detail and prototypes for experimental studies are presented. It is shown that the handling of ﬁnepowders can be improved by using low-frequency, high-frequency or a combination of low- andhigh-frequency vibration.
Keywords: powder handling; ﬂowability; dosing; transport; mixing; dispersion; piezoelectricactuators; vibrations

Numerical and statistical investigation of weld formation in a novel two-dimensional copper-copper bonding process - Dymel, Collin; Eichwald, Paul; Schemmel, Reinhard; Hemsel, Tobias; Brökelmann, Michael; Hunstig, Matthias; Sextro, Walter ((Proceedings of 7th Electronics System-Integration Technology Conference, Dresden, Germany))
State-of-the-art industrial compact high power electronic packages require copper-copper interconnections with larger cross sections made by ultrasonic bonding. In comparison to aluminium-copper, copper-copper interconnections require increased normal forces and ultrasonic power, which might lead to substrate damage due to increased mechanical stresses. One option to raise friction energy without increasing vibration amplitude between wire and substrate or bonding force is the use of two-dimensional vibration. The first part of this contribution reports on the development of a novel bonding system that executes two-dimensional vibrations of a tool-tip to bond a nail- like pin onto a copper substrate. Since intermetallic bonds only form properly when surfaces are clean, oxide free and activated, the geometries of tool-tip and pin were optimised using finite element analysis. To maximize the area of the bonded annulus the distribution of normal pressure was optimized by varying the convexity of the bottom side of the pin. Second, a statistical model obtained from an experimental parameter study shows the influence of different bonding parameters on the bond result. To find bonding parameters with the minimum number of tests, the experiments have been planned using a D-optimal experimental design approach.
Keywords: ultrasonic wire-bonding; bond-tool design; parameter identification; statistical engineering

Experimental investigations on the impact of bond process parameters in two-dimensional ultrasonic copper bonding - Dymel, Collin; Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias ((Proceedings of 8th Electronics IEEE CPMT Symposium Japan (ICSJ 2018), Kyoto, Japan))
Ultrasonic bonding and welding are common friction based approaches in the assembly of power electronics. Interconnections with cross-sections of 0.3 mm² up to 12 mm² made from copper are well suited in high power applications. For increasing friction energy, which is responsible for bond formation, a two-dimensional vibration approach is applied to newly developed interconnection pins. Using two-dimensional vibration for bonding requires identification of suitable bonding parameters. Even though simulation models of wire bonding processes exist, parameters for the two-dimensional pin-bonding process cannot be derived accurately yet. Within this contribution, a methodology and workflow for experimental studies identifying a suitable bond parameter space are presented. The results of a pre-study are used to set up an extensive statistical parameter study, which gives insights about the bond strength change due to bond process parameter variation. By evaluation of electrical data captured during bonding, errors biasing the resulting shear forces are identified. All data obtained during the experimental study is used to build a statistical regression model suitable for predicting shear forces. The accuracy of the regression model’s predictions is determined and the applicability to predict process parameters or validate simulation models is assessed. Finally, the influence of the tool trajectory on the bond formation is determined, comparing one dimensional, elliptic and circular trajectories.
Keywords: ultrasonic two-dimensional bonding; electrical interconnection; process parameters

Numerical and experimental investigations in ultrasonic heavy wire bonding - Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter (6th European Conference on Computational Mechanics (ECCM 6))
Ultrasonic wedge/wedge-wire bonding is used to connect electrical terminals of semiconductor modules in power electronics. The wire is clamped with a tool by a normal force and ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes contaminations like oxide layers are removed from the contact zone and the surface roughness is reduced, thus the real contact area is increased. In the next step of bond formation, thermomechanical forces create micro-junctions between the wire and substrate and the bond strength increases. The bond parameters like the bond normal force, the ultrasonic vibration amplitude and the geometry of the clamping tool show a high influence on the strength and reliability of the wire bond and need to be investigated in detail. Therefore, in this contribution the dynamical behaviour of the ultrasonic system, the wire and the substrate are modeled in form of substructures, which are connected by the friction contacts between tool and wire and between wire and substrate. Approaches for modelling the time variant contact behaviour, the substrate dynamics, and the model order reduction for a time efficient simulation are described to simulate the full bonding process.

Analysis of pipe vibration in an ultrasonic powder transportationsystem - Dunst, Paul; Hemsel, Tobias; Sextro, Walter (elsevier)
The transportation of dry fine powders is an emerging technologic task, as in biotechnology, pharmaceu-tical and coatings industry the particle sizes of processed powders get smaller and smaller. Fine powdersare primarily defined by the fact that adhesive and cohesive forces outweigh the weight forces, leadingto mostly unwanted agglomeration (clumping) and adhesion to surfaces. Thereby it gets more difficult touse conventional conveyor systems (e.g. pneumatic or vibratory conveyors) for transport. A rather newmethod for transporting these fine powders is based on ultrasonic vibrations, which are used to reducefriction between powder and substrate. Within this contribution an experimental set-up consisting of apipe, a solenoid actuator for axial vibration and an annular piezoelectric actuator for the high frequencyradial vibration of the pipe is described. Since amplitudes of the radial pipe vibration should be as large aspossible to get high effects of friction reduction, the pipe is excited to vibrate in resonance. To determinethe optimum excitation frequency and actuator position the vibration modes and resonance frequenciesof the pipe are calculated and measured. Results are in good accordance.
Keywords: Powder transport Piezoelectrics Ultrasonics Pipe vibration Finite element simulation Fine powder

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

MoRFUS: Mobile Reinigungseinheit für Förderketten basierend auf Ultraschall - Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter (43. Deutsche Jahrestagung für Akustik)
ln der industriellen Fertigung werden zum Transport von Bauteilen häufig Förderketten genutzt. Obwohl die Förderketten meist nicht direkt mit den Arbeitsmedien in Berührung kommen, werden sie indirekt durch vagabundierende Stäube und Pulver, die an der geölten Kette anhaften, im Laufe der Zeit stark verschmutzt. Ein derart im Betrieb verschmutztes Kettenglied ist in Abbildung 1 dargestellt. Um die Lebensdauer der Ketten zu erhöhen und das Herunterfallen von Schmutzpartikel auf die Produkte zu vermeiden, muss die Kette regelmäßig gereinigt werden. Ziel des hier beschriebenen Forschungsvorhabens ist die Entwicklung eines Systems, das in der Lage ist, ein einzelnes Kettenglied in unter 60 s mittels Ultraschall zu reinigen. In [1] wurde in ersten Versuchen nachgewiesen, dass Stabschwinger in Abhängigkeit des Sonotrodenabstands zum Reinigungsobjekt und der Ultraschallamplitude eine intensive Reinigungswirkung entfalten. Das Konzept der Reinigungsanlage sieht deshalb vor, im ersten Schritt die stark verschmutzten Kettenglieder durch ein hochintensives Kavitationsfeld von direkt eingetauchten Stabschwingern vorzureinigen und anschließend schwer zugängliche Be- reiche wie Hinterschneidungen oder Bohrungen mittels konventioneller Tauchschwinger von Verschmutzungen zu befreien. Für den Stabschwinger wird die sogenannte - Sonotrode untersucht; diese wird unter anderem auch in der Sonochemie verwendet. Ein wesentliches Merkmal der Sonotrode ist eine hohe Amplitudenübersetzung bei einer gleichzeitig großen Abstrahlfläche. Neben dem Entwurf mittels der L /2 -Synthese wird die Reinigungswirkung der Sonotrode in Abhängigkeit der Ultraschallamplitude und dem Abstand zum Reinigungsobjekt in einer Versuchsreihe untersucht. Zur genaueren Betrachtung der Reinigungs- mechanismen eines Stabschwingers werden abschließend Hochgeschwindigkeitsaufnahmen vorgestellt und analysieren.
Keywords: wire bonding; dynamic behavior; modeling

Transportation of dry fine powders by coordinated friction manipulation - Dunst, Paul; Sextro, Walter; Bornmann, Peter; Hemsel, Tobias; Littmann, Walter (PAMM Proc. Appl. Math. Mech. 16)
The transportation of dry fine powders is an emerging technologic task, as in biotechnology, pharmaceutical or coatings industry particle sizes of processed powders are getting smaller and smaller. Fine powders are primarily defined by the fact that adhesive and cohesive forces outweigh the weight forces. This leads to mostly unwanted agglomeration (clumping) and adhesion to surfaces, what makes it more difficult to use conventional conveyor systems (e. g. pneumatic or vibratory conveyors) for transport. A rather new method for transporting these fine powders is based on ultrasonic vibrations, which are used to reduce friction and adhesion between powder and the substrate. One very effective set-up consists of a pipe, which vibrates harmoniously in axial direction at low frequency combined with a pulsed radial high frequency vibration. The high frequency vibration accelerates the particles perpendicular to the surface of the pipe, which in average leads to lower normal and thereby smaller friction force. With coordinated friction manipulation the powder acceleration can be varied so that the powder may be greatly accelerated and only slightly decelerated in each excitation period of the low frequency axial vibration of the pipe. The amount of powder flow is adjustable by vibration amplitudes, frequencies, and pulse rate, which makes the device versatile for comparable high volume and fine dosing using one setup. Within this contribution an experimental set-up consisting of a pipe, a solenoid actuator for axial vibration and a piezoelectric actuator for the radial high frequency vibration is described. An analytical model is shown, that simulates the powder velocity. Finally, simulation results are validated by experimental data for different driving parameters such as amplitude of low frequency vibration, pipe material and inclination angle.

Kavitationsdetektion mittels Self-Sensing-Ultraschallwandler - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (tm - Technisches Messen)
Eine Vielzahl von Prozessen in der Chemie und Verfahrenstechnik kann durch Ultraschall positiv beeinflusst werden. Oftmals ist ultraschallinduzierte Kavitation der Hauptwirkmechanismus für die positiven Effekte der Beschallung. Daher ist es notwendig die Kavitationsaktivität während des Prozesses zu quantifizieren um die Beschallung für den jeweiligen Prozess optimal gestalten und überwachen zu können. Eine Möglichkeit der prozessbegleitenden Kavitationsdetektion ist die Auswertung der akustischen Emissionen von oszillierenden und kollabierenden Kavitationsblasen mittels Drucksensoren in der Flüssigkeit. Raue Prozessrandbedingungen wie hohe Temperaturen oder aggressive Flüssigkeiten erschweren es jedoch geeignete Sensoren zu finden. Als Alternative wurde daher die Nutzbarkeit der Rückwirkung von Kavitationsereignissen auf das elektrische Eingansgssignal des Ultraschallwandlers zur Quantifizierung von Kavitation untersucht. Die experimentelle Analyse hat ergeben, dass das Einsetzen und in einigen Fällen auch die Art der Kavitation auf Basis der Rückwirkung auf das Stromsignal des Ultraschallwandlers bestimmt werden kann. Die Stärke der Kavitation war hingegen nicht aus den Stromsignalen abzuleiten.
Keywords: Kavitationsdetektion; Self-Sensing; So- nochemie; Ultraschallwandler

Thick KNbO 3 films deposited by ultrasonic-assisted hydrothermal method - Kudo, Ryo; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Acoustical Science and Technology)

Improving the bond quality of copper wire bonds using a friction model approach - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (Electronic Components and Technology Conference (ECTC), 2014 IEEE 64th)
In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production. To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level where van der Waals forces are able to arise between atoms. Also, enough friction energy referred to the total contact area has to be generated to activate the surfaces. Therefore, a friction model is used to simulate the joining process. This model calculates the resulting energy of partial areas in the contact surface and provides information about the adhesion process of each area. The focus here is on the arising of micro joints in the contact area depending on the location in the contact and time. To validate the model, different touchdown forces are used to vary the initial contact areas of wire and substrate. Additionally, a piezoelectric tri-axial force sensor is built up to identify the known phases of pre-deforming, cleaning, adhering and diffusing for the real bonding process to map with the model. Test substrates as DBC and copper plate are used to show the different formations of a wedge bond connection due to hardness and reaction propensity. The experiments were done by using 500 $μ$m copper wire and a standard V-groove tool.
Keywords: adhesion; circuit reliability; deformation; diffusion; fatigue cracks; friction; interconnections; lead bonding; van der Waals forces; Cu; adhering process; adhesion process; ampacity improvement; bond quality improvement; cleaning process; diffusing process; fatigue fracture failure; friction energy; friction model; heat dissipation; mechanical strength; piezoelectric triaxial force sensor; predeforming process; size 500 mum; total contact area; van der Waals forces; wedge copper wire bonding; Bonding; Copper; Finite element analysis; Force; Friction; Substrates; Wires

Self-Sensing Ultrasound Transducer for Cavitation Detection - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (2014 IEEE International Ultrasonics Symposium Proceedings)
Cavitation monitoring is desired to optimize the sonication for diverse sonochemical processes and to detect changes or malfunctions during operation. In situ cavitation measurements can be carried out by detection of the acoustic emissions of cavitation bubbles by sensors in the liquid. However, in harsh environments sensors might not be applicable. Thus, the impact of cavitation on the electrical signals of a piezoelectric transducer has been analyzed as alternative method to measure the threshold, strength and type of cavitation. The applicability has been tested in three different setups to evaluate the general- izability of extracted indicators. In all setups indicators for the cavitation thresholds could be derived from the current signal. In two setups features showed two thresholds that may be linked to the types of cavitation. However, only one feature derived from the current signal in one particular setup correlated to the strength of cavitation. Cavitation detection based on the current signal of the transducer is a useful method to detect cavitation in harsh environments and without perturbing the sound field. Once appli- cable indicators have been identified, they may easily be tracked during the process. However, for more detailed studies about the cavitation activity and its spatial distribution, measurements with in situ sensors are recommended.

Reliability analysis of ultrasonic power transducers - Hemsel, Tobias; Bornmann, Peter; Morita, Takeshi; Sondermann-Wölke, Christoph; Sextro, Walter (Archive of Applied Mechanics)
Keywords: Reliability; Ultrasonic power transducers; FMEA

High-velocity operation of piezoelectric inertia motors: experimental validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Archive of Applied Mechanics)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. It has been shown previously in theoretical investigations that higher velocities and smoother movements can be obtained if these steps do not contain phases of stiction (''stick-slip`` operation), but use sliding friction only (''slip-slip`` operation). One very promising driving option for such motors is the superposition of multiple sinusoidal signals or harmonics. In this contribution, the theoretical results are validated experimentally. In this context, a quick and reliable identification process for parameters describing the friction contact is proposed. Additionally, the force generation potential of inertia motors is investigated theoretically and experimentally. The experimental results confirm the theoretical result that for a given maximum frequency, a signal with a high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion, while the maximum motor force is obtained with signals containing more harmonics. These results are of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Inertia motor; High velocity; Stick-slip motor; Slip-slip operation; Friction parameter identification

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

Increasing the power of piezoelectric energy harvesters by magnetic stiffening - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
A piezoelectric cantilever beam with a tip mass at its free end is a common energy harvester configuration. This article introduces a new principle of designing such a harvester that increases the generated power without changing the resonance frequency of the harvester: the attraction force between two permanent magnets is used to add stiffness to the system. This magnetic stiffening counters the effect of the tip mass on the efficient operation frequency. Five set-ups incorporating piezoelectric bimorph cantilevers of the same type in different mechanical configurations are compared theoretically and experimentally to investigate the feasibility of this principle: theoretical and experimental results show that magnetically stiffened harvesters have important advantages over conventional set-ups with and without tip mass. They generate more power while only slightly increasing the deflection in the piezoelectric harvester and they can be tuned across a wide range of excitation frequencies.

Enhanced energy harvesting using multiple piezoelectric elements: Theory and experiments - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Power and bandwidth of piezoelectric harvesters can be increased by using multiple piezoelectric elements in one harvester. In this contribution, a novel energy harvesting cantilever array with magnetic tuning including three piezoelectric bimorphs is investigated theoretically and experimentally, with a good agreement between model and experiment. Other than harvester designs proposed before, this array is easy to manufacture and insensitive to manufacturing tolerances because its optimum operation frequency can be re-adjusted after fabrication. Using the superposition principle, the Butterworth-Van Dyke model and a mechanical lumped parameters model, the generated voltage and current are determined analytically. Formulas for calculating the power generated by array harvesters with an arbitrary number of piezoelectric elements connected in series or in parallel are derived. It is shown that optimum harvester design must take both the connected load and the operating frequency into account. Strategies for connecting multiple bimorphs to increase the maximum generated power and/or enhance the bandwidth compared to a single bimorph harvester are investigated. For bandwidth enhancement it is essential that individual rectifiers are used for the bimorphs. An example with three bimorphs shows that, depending on the chosen tuning strategy, the power is increased by about 340% or the bandwidth is increased by about 500%, compared to one single bimorph.
Keywords: Energy harvesting; Cantilever array; Bandwidth; Power increase

Characteristics of Piezoelectric Energy Harvesters in Autonomous Systems - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop, Hannover, Germany, 14.-17.7.2013)
A basic autonomous system powered by a piezoelectric harvester contains three components apart from the harvester: a fullwave rectifier, a reservoir capacitor and an electronic device performing the primary task of the system. In this contribution, a model describing the operation of such a system is derived. It is found that in steady-state operation, the piezoelectric harvester experiences two alternating load conditions due to the rectification process. These alternating load conditions can have a significant effect on the operation of the harvester and must be considered in the design of autonomous systems. The results also show that such an autonomous system works efficiently if it is connected to a high impedance load and excited by a frequency matching the anti-resonance frequency of the piezoelectric harvester.
Keywords: Energy harvesting; harvester modeling; load dependence; generated voltage

A friction based approach for modeling wire bonding - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (IMAPS 2013, 46th International Symposium on Microelectronics)
A model approach for wedge/wedge bonding copper wire is presented. The connection between wire and substrate is based on a variety of physical effects, but the dominant one is the friction based welding while applying ultrasound. Consequently, a friction model was used to investigate the welding process. This model is built up universal and can be used to describe the formation of micro welds in the time variant contact area between wire and substrate. Aim of the model is to identify the interactions between touchdown, bond normal force, ultrasonic power and bonding time. To do so, the contact area is discretized into partial areas where a Point Contact Model is applied. Based on this approach it is possible to simulate micro and macro slip inside the contact area between wire and substrate. The work done by friction force is a main criterion to define occurring micro joints which influence the subsequent welding.
Keywords: Wire bonding; friction modeling; wire bond quality; contact element modeling

Leistungs- und Bandbreitensteigerung von Energy-Harvesting-Generatoren für Energieautarke Systeme - Hunstig, Matthias; Al-Ashtari, Waleed; Hemsel, Tobias; Sextro, Walter (9. Paderborner Workshop Entwurf mechatronischer Systeme)

High-Velocity Slip-Slip Operation of Piezoelectric Inertia Motors - Experimental Validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop)
It has been shown previously that ``slip-slip'' operation of piezoelectric inertia motors allows higher velocities and smoother movements than classic ``stick-slip'' operation. One very promising driving option is to use a superposition of multiple sinusoidal signals. In this contribution, previous theoretical results are validated experimentally. The results confirm the theoretical result that for a given maximum frequency, usually defined by the actuator characteristics, a signal with high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion. This result is of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Piezoelectric inertia motor; stick-slip motor; driving signal; velocity; smoothness

Modelling the friction contact in an inertia motor - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric inertia motors, also known as stickslip drives or (smooth) impact drives, use the inertia of a body to drive it by a friction contact in small steps, in the majority of motors composed of a stick phase and a slip phase between the friction partners. For optimizing inertia motors, it is important to understand the friction contact correctly and to measure its properties appropriately. This contribution presents experimental set-ups for measuring the contact force, friction force and relative displacement in an actual inertia motor with a dry friction contact and numerical simulations of the motor operation. The motor uses a pre-stressed multilayer actuator with a displacement in the range of 20 $μ$ m. It is shown that a previously postulated condition for the applicability of simple kinetic friction models is well fulfilled for the investigated motor. The friction contact in the motor is simulated using different kinetic friction models. The input for the friction models is the measured motion of the rod. The models qualitatively reproduce the measured motion but show quantitative deviations varying with frequency. These can be explained by vibrations of the driving rod that are experimentally investigated.
Keywords: Actuator; friction; motor; piezoelectric

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part II: Frequency-limited excitation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
This contribution provides a systematic investigation and performance comparison of different modes of operation for piezoelectric inertia drives. The movement of these motors is classically assumed to consist of steps involving stiction and sliding, resulting in the term ``stick-slip drives''. In the first part of this contribution it has been found that using ideal driving signals, ``slip-slip'' operation without phases of stiction allows very high velocities, while the maximum velocity is limited principally in stick-slip operation. In this part it is shown that slip-slip operation is also suitable for use with real actuators, driven with frequency-limited versions of the ideal signals presented in part I. The motional performance of the motor as well as its wear and the required electric power are investigated for operation with different signals. It is found that for high velocity inertia motors it is recommendable to use actuators with large stroke and to drive them with a signal consisting of two harmonics at a high fundamental frequency, a result that is supported by similar setups implemented experimentally by other authors. Using Lanczos' σ factors to calculate the frequency-limited excitation signals instead of standard Fourier series additionally increases the motor performance significantly. The results help motor designers to choose the appropriate mode of operation and to optimise the motor parameters for their individual applications.
Keywords: Inertia motor

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part I: Ideal Excitation. - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Piezoelectric inertia motors, also known as ``stick--slip drives'', use the inertia of a body to drive it in small steps by means of a friction contact. While these steps are classically assumed to involve stiction and sliding, the motors can also operate in ``slip--slip'' mode without any phase of static friction. This contribution provides a systematic investigation and performance comparison of different stick--slip and slip--slip modes of operation. Different criteria for comparing the motional performance of inertia motors are defined: Steady state velocity, smoothness of motion, and start-up time. Using the example of a translational inertia motor excited by an ideal displacement signal, it is found that the maximum velocity reachable in stick--slip operation is limited principally, while continuous slip--slip operation allows very high velocities. For the investigated driving signals, the motor velocity is proportional to the square root of the actuator stroke. The motor performance with these ideal signals defines an upper boundary for the performance of real motors.
Keywords: Inertia motor; Stick--slip drive; Mode of operation; Performance indicator; Velocity maximization; Actuator stroke

Selected Papers from the 9th International Workshop on Piezoelectric Materials and Applications in Actuators (Sensors and Actuators A: Physical)
The 9th International Workshop on Piezoelectric Materials and Applications in Actuators (IWPMA 2012) was successfully held on 22–25 April 2012 in Hirosaki, Japan. The general chair was Prof. M.K. Kurosawa from the Tokyo Institute of Technology, Japan. In the past, Korea, Germany, Turkey, China, and USA have hosted the annual conference, but this was the first time for the annual IWPMA conference to be held in Japan. The IWPMA 2012 was organized as a joint symposium with JTTAS Smart Actuator/Sensor Study Committee and ICAT International Actuator Symposium. More than 150 people from the world (12 countries) participated and had fruitful discussions with 138 presentations including 11 invited talks. In addition to piezoelectric materials and piezoelectric actuators, the presentation topics were expanded to include solid-state actuators, energy harvesting, multifunctional materials, and other current important issues. It is our honor to pronounce that the “Sensors and Actuators A” journal has published this special issue on the IWPMA 2012 including the best 25 contributions. This issue covers the functional materials, such as piezoelectric and magnetostrictive materials, and their applications. However, for the innovative devices, various ideas concerning materials, mechanisms, designs, fabrication process, and control-systems are also required to be organically combined. From the view of this concept, we believe the published 25 papers can excite the researcher's intellectual curiosity concerning these issues and can serve as the driving force for further breakthroughs. Please enjoy the latest research results selected by our editor team. Finally, we appreciate all participants in the IWPMA 2012 and the devoted reviewers for the publication. We hope that the papers in this special issue will open up the next researches, which will be presented in the future IWPMA conferences.

Study on optimizing ultrasonic irradiation period for thick polycrystalline PZT film by hydrothermal method - Ohta, Kanako; Isobe, Gaku; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics)
The hydrothermal method utilizes a solution-based chemical reaction to synthesize piezoelectric thin films and powders. This method has a number of advantages, such as low-temperature synthesis, and high purity and high quality of the product. In order to promote hydrothermal reactions, we developed an ultrasonic assisted hydrothermal method and confirmed that it produces dense and thick lead--zirconate--titanate (PZT) films. In the hydrothermal method, a crystal growth process follows the nucleation process. In this study, we verified that ultrasonic irradiation is effective for the nucleation process, and there is an optimum irradiation period to obtain thicker PZT films. With this optimization, a 9.2-$μ$ m-thick PZT polycrystalline film was obtained in a single deposition process. For this film, ultrasonic irradiation was carried out from the beginning of the reaction for 18 h, followed by a 6 h deposition without ultrasonic irradiation. These results indicate that the ultrasonic irradiation mainly promotes the nucleation process.
Keywords: Piezoelectric material

Piezoelectric Properties of CuO-Doped (K,Na)NbO3 Lead-Free Ceramics Synthesized with Hydrothermal Powders - Yokouchi, Yuriko; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
We report the piezoelectric properties of CuO-doped hydrothermal (K,Na)NbO3 ceramics that can be applied as hard-type lead-free piezoelectric ceramics. To date, we have succeeded in synthesizing high-quality KNbO3 and NaNbO3 powders by the hydrothermal method, which is based on an ionic reaction at high temperature (around 210 $\,^{°}$C) and pressure. Increasing both the piezoelectric constant d and the mechanical quality factor (Qm) is important for resonance-type piezoelectric devices, such as ultrasonic motors and transformers. CuO doping into hydrothermal (K,Na)NbO3 ceramics was examined to realize hard-type lead-free piezoelectric ceramics. By doping with 1.2 mol % CuO, Qm was increased and the dielectric loss (tan δ) was decreased to 0.5%. The grain size was also influenced by the amount of CuO doping, which indicates that Qm is related to the density. To achieve a higher Qm value, the grain size is required to be less than 5 µm; however, excessive CuO doping leads to anomalous grain growth. Optimal piezoelectric properties were obtained for 1.2 mol % CuO-doped (K,Na)NbO3; k31 = 0.32, d31 = -44 pC/N, Qm (radial) = 959, and tan δ= 0.5%. These characteristics showed that CuO doping with hydrothermal powders is effective for obtaining hard-type ceramics, and the mechanical quality factor is more than ten times higher than that of nondoped hydrothermal (K,Na)NbO3 ceramics. Therefore, compared with the conventional solid-state method, we could succeed in obtaining hard-type ceramics by a simple and short process.

Frequency tuning of piezoelectric energy harvesters by magnetic force - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Smart Materials and Structures)
A piezoelectric energy harvester is an electromechanical device that converts ambient mechanical vibration into electric power. Most existing vibration energy harvesting devices operate effectively at a single frequency only, dictated by the design of the device. This frequency must match the frequency of the host structure vibration. However, real world structural vibrations rarely have a specific constant frequency. Therefore, piezoelectric harvesters that generate usable power across a range of exciting frequencies are required to make this technology commercially viable. Currently known harvester tuning techniques have many limitations, in particular they miss the ability to work during harvester operation and most often cannot perform a precise tuning. This paper describes the design and testing of a vibration energy harvester with tunable resonance frequency, wherein the tuning is accomplished by changing the attraction force between two permanent magnets by adjusting the distance between the magnets. This tuning technique allows the natural frequency to be manipulated before and during operation of the harvester. Furthermore the paper presents a physical description of the frequency tuning effect. The experimental results achieved with a piezoelectric bimorph fit the calculated results very well. The calculation and experimental results show that using this tuning technique the natural frequency of the harvester can be varied efficiently within a wide range: in the test setup, the natural frequency of the piezoelectric bimorph could be increased by more than 70%.

Analytical determination of characteristic frequencies and equivalent circuit parameters of a piezoelectric bimorph - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric structures are nowadays used in many different applications. A better understanding of the influence of material properties and geometrical design on the performance of these structures helps to develop piezoelectric structures specifically designed for their application. Different equivalent circuits have been introduced in the literature to investigate the behaviour of piezoelectric transducers. The model parameters are usually determined from measurements covering the characteristic frequencies of the piezoelectric transducer. This article introduces an analytical technique for calculating the mechanical and electrical equivalent system parameters and characteristic frequencies based on material properties and geometry for a cantilever bimorph structure. The model is validated by measurements using a cantilever bimorph and fits the experimental results better than previous models. The model gives a full set of piezoelectric transducer parameters and is therefore well suited for further theoretical investigations of piezoelectric transducers for different applications. The results also show that even small manufacturing tolerances have a considerable effect on the system parameters and characteristic frequencies. This might lead to intolerable deviations, especially in dynamic applications and should be avoided by careful design and production.

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

An efficient simulation technique for high-frequency piezoelectric inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Ultrasonics Symposium (IUS), 2012 IEEE International)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. These motors can operate in ``stick-slip'' or ``slip-slip'' mode, with the fundamental frequency of the driving signal ranging from several Hertz to more than 100 kHz. To predict the motor characteristics, a Coulomb friction model is sufficient in many cases, but numerical simulation requires microscopic time steps. This contribution proposes a much faster simulation technique using one evaluation per period of the excitation signal. The proposed technique produces results very close to those of timestep simulation for ultrasonics inertia motors and allows direct determination of the steady-state velocity of an inertia motor from the motion profile of the driving part. Thus it is a useful simulation technique which can be applied in both analysis and design of inertia motors, especially for parameter studies and optimisation.
Keywords: friction; ultrasonic motors; Coulomb friction model; efficient simulation technique; friction contact; high-frequency piezoelectric inertia motor; motor characteristics prediction; numerical simulation; slip-slip mode; stick-slip mode; time-step simulation; ultrasonic inertia motor; Acceleration; Acoustics; Actuators; Computational modeling; Friction; Numerical models; Steady-state